Technical Note: Single‐pulse beam characterization for FLASH‐RT using optical imaging in a water tank. Issue 5 (31st March 2021) - Ashraf, M. Ramish; Rahman, Mahbubur; Zhang, Rongxiao; Cao, Xu; Williams, Benjamin B.; Hoopes, P. Jack; Gladstone, David J.; Pogue, Brian W.; Bruza, Petr
Abstract : Purpose: High dose rate conditions, coupled with problems related to small field dosimetry, make dose characterization for FLASH‐RT challenging. Most conventional dosimeters show significant dependence on dose rate at ultra‐high dose rate conditions or fail to provide sufficiently fast temporal data for pulse to pulse dosimetry. Here fast 2D imaging of radioluminescence from a water and quinine phantom was tested for dosimetry of individual 4 μs linac pulses. Methods: A modified clinical linac delivered an electron FLASH beam of >50 Gy/s to clinical isocenter. This modification removed the x‐ray target and flattening filter, leading to a beam that was symmetric and gaussian, as verified with GafChromic EBT‐XD film. Lateral projected 2D dose distributions for each linac pulse were imaged in a quinine‐doped water tank using a gated intensified camera, and an inverse Abel transform reconstruction provided 3D images for on‐axis depth dose values. A total of 20 pulses were delivered with a 10 MeV, 1.5 cm circular beam, and beam with jaws wide open (40 × 40 cm 2 ), and a 3D dose distribution was recovered for each pulse. Beam output was analyzed on a pulse by pulse basis. Results: The Rp, Dmax, and the R50 measured with film and optical methods agreed to within 1 mm for the 1.5 cm circular beam and the beam with jaws wide open. Cross beam profiles for both beams agreed with film data with >95% passing rate (2%/2 mm gamma criteria). The optical central axis depth dose agreed with film data, except for near the surface. A temporal pulse analysis revealed a ramp‐up period where the dose per pulse increased for the first few pulses and then stabilized. Conclusions: Optical imaging of radioluminescence was presented as a valuable tool for establishing a baseline for the recently initiated electron FLASH beam at our institution.